Effect of Core Stability Exercises in Reducing Complaints of Low Back Pain on the Pembatik Across the City of Jambi - Putra Hadi; Wanti Hasmar (Indonesian Journal of Sport Management and Physical Education, 2022)
Batik craftsmen tend to be in a long sitting position, followed by a batik position that is not ergonomic, the way they work, all of which still use the manual method, of course, will cause a lot of complaints or skeletal muscle disorders. So far, batik makers usually treat low back pain by resting without any treatment. There is a need for physiotherapy modalities that can be applied to batik, such as core stability. To analyze the effect of core stability exercise in lowering the lower back in the batik group Seberang Jambi City. This type of research is a quasi-experimental research with pre-test and post-test with control group design. The research sample amounted to 20 respondents. The measuring instrument uses the Visual Analog Scale (VAS). The data analysis technique used Paired Sample T-Test and Independent Sample T-Test. There was a significant effect on the core stability exercise group in lowering the lower back. There is a difference in the effect of core stability exercises in lowering the lower back on batik at the Kajang Lako Seberang Cooperative, Jambi City.